The Absence of National Disaster Declaration in Sumatra Floods 2025: Maqasid Syariah Perspective and Economic Impact - Andri Rivai; Fachri Rinaldy; Edy Saputra; Diah Mutiara Kartika (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2026)
Objective: This study examines the implications of the absence of a national disaster declaration during the 2025 Sumatra floods by analysing its juridical validity, governance consequences, and economic impacts through the lens of Maqasid Syariah. The study addresses a gap in disaster governance literature by investigating policy inaction as a determinant of welfare deficits and post-disaster economic vulnerability. Method: This research employs a qualitative socio-legal approach integrating normative legal analysis, disaster governance evaluation, and regional economic assessment. Data were collected from disaster management regulations, government reports, statistical publications, policy documents, and relevant academic literature. The data were analysed using content analysis and the Maqasid Syariah framework. Result: The findings indicate that the 2025 Sumatra floods substantively fulfilled the legal indicators for a national disaster declaration under Law No. 24 of 2007. However, the absence of such a declaration weakened coordination, delayed resource mobilisation, and reduced the effectiveness of humanitarian and recovery interventions. From a Maqasid Syariah perspective, this policy inaction generated deficits in the protection of life, wealth, intellect, lineage, religion, and the environment. Economically, it contributed to prolonged recovery, disrupted investment, and increased regional vulnerability. Implication: Integrating Maqasid Syariah into disaster governance can strengthen welfare-oriented policy evaluation, improve recovery effectiveness, and enhance socio-economic resilience. Originality or Novelty: This study conceptualises policy inaction as a form of disaster-governance failure and analyses its implications using an integrated framework linking Maqasid Syariah, disaster governance, and regional economic recovery.